Association Between Wine Consumption and Cognitive Decline in Older People: A Systematic Review and Meta-Analysis of Longitudinal Studies - Lucerón-Lucas-Torres, Maribel; Cavero-Redondo, Iván; Martínez-Vizcaíno, Vicente; Saz-Lara, Alicia; Pascual-Morena, Carlos; Álvarez-Bueno, Celia (Frontiers in Nutrition, 2022)
Background. Low to moderate alcohol consumption appears to have potential health benefits. Existing evidence concludes that wine may be associated with a lower incidence of certain diseases. This systematic review and meta-analysis aims to examine evidence on the association between wine consumption and cognitive decline, and to analyse whether this association varies depending on the wine consumption level or is affected by individual and study characteristics, including mean age, percentage of women participants, and follow-up time. Methods. In this systematic review and meta-analysis we undertook a search in MEDLINE (via PubMed), Scopus, Cochrane, and Web of Science databases for longitudinal studies measuring the association between wine consumption and cognitive decline from their inception to May, 2021. Effect sizes were calculated using the DerSimonian and Laird and Hartung-Knapp-Sidik-Jonkman methods. Results. The search retrieved 6055 articles, 14 of which were included in this systematic review. Ten studies were included in the meta-analysis. The studies were published between 1997 and 2019. They were conducted in nine different countries. The sample size of the included studies ranged from 360 to 10,308 with a mean age of 68 years old. Using the DerSimoniand and Laird method, the pooled RR for the effect of wine consumption on cognitive decline was 0.75 (95% CI: 0.67-0.84; I2= 81.2%; τ2: 0.0131). Using the Hartung-Knapp-Sidik-Jonkman method, the RR was 0.68 (95% CI: 0.53-0.82; I2= 81.2%; τ2: 0.066). Conclusions. This study may show protective effect of wine consumption against cognitive decline. However, it would be important for future research to differentiate the types of wine within consumption.